2021
DOI: 10.3389/fvets.2021.652351
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Antibiotic Resistance in Isolates From Diseased Livestock

Abstract: Overuse of antimicrobials in livestock health and production beyond therapeutic needs has been highlighted in recent years as one of the major risk factors for the acceleration of antimicrobial resistance (AMR) of bacteria in both humans and animals. While there is an abundance of reports on AMR in clinical isolates from humans, information regarding the patterns of resistance in clinical isolates from animals is scarce. Hence, a situational analysis of AMR based on clinical isolates from a veterinary diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 53 publications
5
38
2
Order By: Relevance
“…However, recent studies have shown increased resistance against tetracycline among S. aureus [ 32 ] and E. coli isolates [ 33 ] from cases of mastitis. There is no doubt that antimicrobial usage in food animal production leads to an increase in AMR [ 34 , 35 ]. Dairy farms may serve as a source of antimicrobial-resistant human pathogenic bacteria, especially extended spectrum beta-lactamases producing E. coli [ 33 , 36 ] and colistin-resistant E. coli [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown increased resistance against tetracycline among S. aureus [ 32 ] and E. coli isolates [ 33 ] from cases of mastitis. There is no doubt that antimicrobial usage in food animal production leads to an increase in AMR [ 34 , 35 ]. Dairy farms may serve as a source of antimicrobial-resistant human pathogenic bacteria, especially extended spectrum beta-lactamases producing E. coli [ 33 , 36 ] and colistin-resistant E. coli [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In low- and middle-income countries (LMICs), 73% of all antimicrobials are used in animals raised for food [ 2 ]. More specifically, in Malaysia and many other Southeast Asian countries, a wide use of antibiotics, especially in intensive production system, is linked to the higher resistance to various antibiotics [ 3 ]. Most of these antimicrobial compounds are accumulated and biomagnified through the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, erythromycin and trimethoprim-sulphamethoxazole resistance was found in 34.78% of isolates. Due to the widespread and inappropriate use of penicillin and other antibiotics in infection treatment in dairy farming and healthcare, the majority of S. aureus strains are resistant to these agents (de los Santos et al 2017;Haulisah et al 2021). In this experiment, the Kirby-Bauer method using MHA standard medium demonstrated high performance to support better growth conditions to spread the suspension of S. aureus in BHI broth.…”
Section: Discussionmentioning
confidence: 89%